The use of gen alpha slang as a persuasive language in Instagram reels marketing - Chen, Valencia (Priviet Social Sciences Journal, 2025)
Social media marketing has been increasingly used to advertise products and services, especially through Instagram Reels. This study investigates how Generation Alpha slang functions as persuasive language in marketing on Instagram Reels. Using a qualitative case study design, 15 influencer Reels were examined through thematic analysis of comments and engagement metrics, including likes, shares, saves and views. The results indicate that reels incorporating Gen Alpha slang and non-fiction storytelling achieved higher engagement rates than those using formal English or rhetorical questions. These findings are interpreted through the Elaboration Likelihood Model, Uses and Gratifications Theory, and Persuasion Theory, which collectively explain how slang operates as a peripheral cue, fulfills social identity needs, and enhances persuasion through increased liking and social proof. While the results provide insight into emerging generational language trends in digital marketing, the study’s scope is limited by its small sample size, convenience sampling, and the absence of intercoder reliability testing. Future research should adopt larger, systematically coded datasets to validate and expand on these findings.